Evaluasi Pembelajaran Bahasa Arab Siswa Kelas IIIA SDIT Mutiara Insani Gatak Delanggu Klaten - Hafshah Khoirunnidda (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2020)
One of the problems often overlooked in Arabic language learning is the evaluation stage of the learning process. This is evident from the declining student achievement each year. At SDIT Mutiara Insani Klaten, 5 out of 28 students scored below the minimum passing grade (KKM). This article summarizes the findings of a study conducted at SDIT Mutiara Insani, which explains the stages of evaluation in Arabic language learning. These stages include the formulation and planning of objectives, the establishment of criteria, the determination of assessment tools, the measurement of success, and the preparation of recommendations and suggestions. This research is a case study and falls under descriptive qualitative research. The methods used were observation, interviews, and documentation. In analyzing the data, the researcher employed the Miles and Huberman model. Observations conducted in class IIIA of SDIT Mutiara Insani showed that the evaluation process had been running effectively. This success was attributed to the direct support and guidance from the school principal, teacher competence, and adequate facilities and infrastructure. However, students’ learning interest, behavior, motivation, and the environmental conditions were found to be inhibiting factors in the evaluation process. This study contributes to the development and serves as a reference to improve the quality of teachers in carrying out their teaching and educational duties, especially in the evaluation of Arabic language learning.